When a Cure Becomes the Crisis: A Rare and Severe Adverse Drug Reaction to Fluoroquinolones Causing Stevens-Johnson Syndrome in an Elderly Male - Ganjala, Hemalatha; Shaik, Uzma Aafreen; Kollipara, Mohana; Padigala, Ramya Jyothi; Dimmiti, Jayasri; Gajula, Ram Nageswara Rao; Yasam, Kiran Sravya; Vinnakota, Dileep Kumar; Jirra, Vijaya Bhaskar; Korikani, Lavanya (Journal of Pharmacy Practice and Community Medicine, 2026)
For the past several years and into the foreseeable future, Fluoroquinolone (FQ) antibiotics have been the most widely used in human health, animal aquaculture, and animal agriculture due to their broad antimicrobial activity in treating respiratory, digestive, stomach, and urinary tract infections. Fluoroquinolones such as levofloxacin, ofloxacin, and ciprofloxacin are broad-spectrum antibiotics that are effective against Gram-negative and moderately active against Gram-positive aerobic bacteria. The most common side effects of fluoroquinolones include gastrointestinal problems and central nervous system issues. These side effects typically appear within the first few days of treatment and often manifest within the first 7-10 days of treatment. In this case, an elderly male patient developed symptoms of Stevens-Johnson syndrome within one day after taking metronidazole and a combination of ofloxacin and ornidazole for loose stools and came to a tertiary care hospital. The diagnosis was confirmed based on a complete blood count, C-reactive protein levels, serum creatinine levels, and the body surface area affected. Diagnosed as mild Stevens-Johnson Syndrome (SJS), the mortality rate was expected to be nearly 12.1% based on the severity-of-Illness Score for Toxic Epidermal Necrolysis (SCORTEN) criteria. And this condition was treated with saline dressings, pain management, steroids, antihistamines, and IV fluids. However, even if it is milder, it is multisystemic, and organs show dangerous symptoms that can lead to life-threatening situations and often death, so careful diagnosis, treatment, and follow-up are needed.
Keywords: Fluoroquinolones; Ofloxacin; SCORTEN criteria; Stevens-Johnson syndrome